2016
DOI: 10.4314/ahs.v16i1.14
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of risky sexual behaviours between circumcised and uncircumcised men aged 30-44 years in Botswana

Abstract: Abstract:Background: The principal mode of HIV transmission in Southern Africa is through sexual intercourse, and this has prompted uptake of safe male circumcision. Engaging in risky sexual behaviour by circumcised men increases the risks of acquiring HIV, though male circumcision coupled with preventive behaviour reduces this risk. Objective: To compare the factors associated with risky sexual behaviour among circumcised and uncircumcised men in Botswana. Methods: Nationally representative data from the Bots… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…Seidu et al [ 15 ] showed in their study that SAM in rural areas had lower odds to pay for sex, compared to men in urban areas. Other studies in Botswana [ 30 ], China [ 31 ], and Cambodia [ 32 ] have also reported that SAM in urban areas are more exposed to STIs due to their higher odds of paying for sex. Disparities in socio-economic and healthcare access between urban and rural areas in SSA could partly explain this trend.…”
Section: Discussionmentioning
confidence: 99%
“…Seidu et al [ 15 ] showed in their study that SAM in rural areas had lower odds to pay for sex, compared to men in urban areas. Other studies in Botswana [ 30 ], China [ 31 ], and Cambodia [ 32 ] have also reported that SAM in urban areas are more exposed to STIs due to their higher odds of paying for sex. Disparities in socio-economic and healthcare access between urban and rural areas in SSA could partly explain this trend.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that men in rural areas had lower odds to pay for sex, compared to men in urban centres, is supported by studies in Botswana ( Balekang & Dintwa, 2016 ), China (Pan, Parish, & Huang, 2011) and Cambodia ( Dizechi et al, 2018 ) where it was found that men in urban areas were significantly more likely to pay for sex. The reason could be that the sex partners of men who pay for sex may be predominant in urban areas.…”
Section: Discussionmentioning
confidence: 78%
“…Previous studies have revealed that socio-demographic, economic and behavioral factors are associated with paid sex among men. The socio-demographic factors include age ( Girchenko et al, 2015 ; Jewkes et al, 2012 ; Rich et al, 2018 ; Rissel et al, 2017 ), educational level ( Choudhry et al, 2015 ; Dizechi et al, 2018 ; Galvan, Ortiz, Martinez, & Bing, 2009 ; Jewkes et al, 2012 ; Pitts, Smith, Grierson, O'brien, & Misson, 2004 ), place of residence ( Balekang and Dintwa, 2016 , Dizechi et al, 2018 , Pan, Parish, & Huang, 2011 ) marital status ( Belza et al, 2008 ; Rissel et al, 2017 ; Schei & Stigum, 2010 ; Ward et al, 2005 ) and wealth status ( Dizechi et al, 2018 ; Jewkes et al, 2012 ; Jones et al, 2015 ; Rich et al, 2018 ). It has also been found that exposure to mass media (newspapers, magazines, radio and television) are associated with risky sexual practices, which may include paid sex ( Asekun-Olarinmoye, Asekun-Olarinmoye, Adebimpe, & Omisore, 2014 ; Bleakley, Hennessy, Fishbein, & Jordan, 2011 ; Fisher, Hill, Grube & Grube, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there was no information about the patients addiction to alcohol, smoke or maybe drug abuse in the SEER database, and these factors can also impact the survival of AML patients [ 41 , 42 ]. The studies by Park B et al and Balekang GB et al have indicated that patients with unmarried status were more prone to such addiction habits [ 43 , 44 ]. So, the physician should pay attention to such adverse factors, particularly in unmarried AML patients.…”
Section: Discussionmentioning
confidence: 99%